Differential Associations Between Posttraumatic Cognitions, Posttraumatic Stress Disorder Symptoms, and Race Among Black and White Veterans Seeking Treatment for Assaultive Military Sexual Trauma - Fernando, Michelle (Journal of interpersonal violence, 2024)
Past research supports the role of negative posttraumatic cognitions (NPCs) in the development and maintenance of posttraumatic stress disorder (PTSD). The relationship between NPCs and PTSD may be uniquely impacted by racial status and experiences of military sexual trauma (MST), both of which may have a unique impact on one’s understanding of self, others, and the world. We explored racial differences in the association between NPCs and PTSD symptom clusters in a sample of veterans endorsing MST (N = 139; 74.8% White, 25.2% Black). A path model was created and analyzed both with the full sample and separately by racial group. In the full sample, NPCs about the self and world were significantly associated with intrusion, negative alterations in cognitions and mood (NACM), and arousal, but not avoidance. Self-blame was not a significant predictor of negative alterations in cognition in mood. This model was consistent in the White veteran model, whereas only negative cognitions about the self were associated with NACM in the Black veteran path model. NPCs about the self and world appear important to non-avoidance PTSD symptomatology related to MST and thus should be targeted in treatment. For Black veterans endorsing distress related to NACM symptoms, negative beliefs about the self should be specifically considered for intervention.